Business is tense: new evidence on how language affects economic activity - Francesco Campo; Luca Nunziata; Lorenzo Rocco (Journal of Economic Growth, 2023)
Abstract We provide a large scale within-country analysis of the effect of language future time reference (FTR) on self-employment using individual-level data from Switzerland, a country characterized by a long-standing multilingualism and a large share of immigrant population. We test the hypothesis that speakers of languages where future tense marking is not obligatory in prediction contexts (defined as weak FTR) may have a closer perception of future rewards and be more willing to become self-employed, a choice that reflects future orientation. We perform an epidemiological analysis which consistently indicates that long-term immigrants who speak weak FTR languages are between 2 and 4 percentage points more likely to be self-employed compared to speakers of strong FTR languages, net of unobservable ancestral cultural traits, districts of destination's characteristics, and linguistic features other than FTR. We find that the effect is largest when the main language of daily use is the mother tongue, but the effect is also significant when the main language is learnt later in life.
Additional information: D15;J24;J6;L26;Z1
Keywords: 330; Self-employment; Entrepreneurship; Language; Future Time Reference; Culture; Migration; Switzerland